2022
DOI: 10.1172/jci156083
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cells from COVID-19 mRNA vaccine recipients recognize a conserved epitope present in diverse coronaviruses

Abstract: Recent studies have shown that vaccinated individuals harbor T cells that can cross-recognize SARS-CoV-2 and endemic human common cold coronaviruses (HCoVs). However, it is still unknown whether CD4+ T cells from vaccinated individuals recognize peptides from bat coronaviruses that may have the potential of causing future pandemics. In this study, we identified a SARS-CoV-2 spike protein epitope (S815-827) that is conserved in coronaviruses from different genera and subgenera including SARS-CoV, MERS-CoV, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Understanding the steady state dynamics of CCC antibody and T cell responses in humans is of potential relevance in the context of the long-term evolution of the SARS-CoV-2 pandemic, in the context of the current scenario, where a large fraction of the human population is exposed and/or vaccinated. Furthermore, it has been widely reported that CCC T cell responses are associated with some degree of cross-reactivity with SARS-CoV-2, and that this cross-reactivity can at least in part explain the pre-existing T cell memory reactivity recognizing SARS-CoV-2 sequences, observed in SARS-CoV-2 unexposed subjects [25][26][27][28][29] . A putative role for CCC cross-reactive T cells in modulating COVID-19 vaccination and disease outcomes has been indicated by several independent studies 26,[30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the steady state dynamics of CCC antibody and T cell responses in humans is of potential relevance in the context of the long-term evolution of the SARS-CoV-2 pandemic, in the context of the current scenario, where a large fraction of the human population is exposed and/or vaccinated. Furthermore, it has been widely reported that CCC T cell responses are associated with some degree of cross-reactivity with SARS-CoV-2, and that this cross-reactivity can at least in part explain the pre-existing T cell memory reactivity recognizing SARS-CoV-2 sequences, observed in SARS-CoV-2 unexposed subjects [25][26][27][28][29] . A putative role for CCC cross-reactive T cells in modulating COVID-19 vaccination and disease outcomes has been indicated by several independent studies 26,[30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been widely reported that CCC T cell responses are associated with some degree of cross-reactivity with SARS-CoV-2, and that this cross-reactivity can at least in part explain the pre-existing T cell memory reactivity recognizing SARS-CoV-2 sequences, observed in SARS-CoV-2 unexposed subjects 2529 . A putative role for CCC cross-reactive T cells in modulating COVID-19 vaccination and disease outcomes has been indicated by several independent studies 26,3033 .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, we studied reactivity against the endemic hCoV, observing immune responses in the majority of healthy and immunocompromised subjects. Interestingly, COVID-19 survivors displayed a broader reactivity pattern against the endemic viruses, suggesting possible induction of cross-reactive immunity upon resolution of COVID-19 that is increasingly recognized in literature[56, 57]. Ex vivo expanded T cells specific for SARS-CoV2 S, M and NP antigens and the equivalent antigens from hCoVs were further tested for cross-reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Both markers indicate that a lower proportion of naive CD4 T cells responds to the vaccine antigen. Indeed, animal and human studies show that mRNA vaccines induce strong CD4 T-cell responses [ 20 , 21 ]. Not unsurprisingly, these markers of T-cell aging did not predict the humoral response.…”
Section: Discussionmentioning
confidence: 99%